2017
DOI: 10.1038/srep43677
|View full text |Cite
|
Sign up to set email alerts
|

Nitrification inhibitors can increase post-harvest nitrous oxide emissions in an intensive vegetable production system

Abstract: To investigate the effect of nitrification inhibitors (NIs) 3,4-dimethylpyrazole phosphate (DMPP) and 3-methylpyrazole 1,2,4-triazole (3MP + TZ), on N2O emissions and yield from a typical vegetable rotation in sub-tropical Australia we monitored soil N2O fluxes continuously over an entire year using an automated greenhouse gas measurement system. The temporal variation of N2O fluxes showed only low emissions over the vegetable cropping phases, but significantly higher emissions were observed post-harvest accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 72 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…this is necessary to obtain precise results for trace gas emissions 28,[68][69][70][71][72] . Future endeavors aimed at quantifying trace gas flux responses to microplastic addition should also rely on such measurements.…”
Section: Oxygen Supply Of the Soil Is Probably The Reason For The Difmentioning
confidence: 99%
“…this is necessary to obtain precise results for trace gas emissions 28,[68][69][70][71][72] . Future endeavors aimed at quantifying trace gas flux responses to microplastic addition should also rely on such measurements.…”
Section: Oxygen Supply Of the Soil Is Probably The Reason For The Difmentioning
confidence: 99%
“…However, this can also decrease the marketable yield for some vegetable crops (Di Mola et al., 2020), so farmers may be reluctant to adopt this strategy. Use of the nitrification inhibitor 3,4‐dimethylpyrazole phosphate (DMPP) has been effective at reducing N 2 O emissions from applied fertilizer‐N in vegetable systems (Lam et al., 2018), but the impact on NUE and vegetable yield is not guaranteed (Pfab et al., 2012; Scheer et al., 2017). Rose et al.…”
Section: Introductionmentioning
confidence: 99%
“…Emission peaks typically make up a considerable portion of annual emissions: up to 90% for freeze–thaw emissions (Wagner‐Riddle et al., 2017), up to 97% postharvest and after summer rainfall in semiarid regions (Barton, Hoyle, Stefanova, & Murphy, 2016), up to 50% within the first weeks after N fertilizer events (Shcherbak et al., 2014), and up to 30% within a few weeks of manure application (Chadwick et al., 2011). Peak events have also been observed during tillage, residue management (Scheer et al., 2017), and irrigation, though these have been less studied and often coincide with N application events.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing gap numbers or gap duration it becomes more likely that gap‐filling will be used over periods where soil conditions and chemistry, and thus emission rates, may change—adding to uncertainty in emission estimates. Beyond the already‐mentioned challenge of underestimating emissions due to missing peak emission events, sampling strategies that do not sample outside of the growing season present issues, as they may be difficult to extrapolate to an annual value or accurate EF (Scheer et al., 2017; Wagner‐Riddle et al., 2017). Although some studies have examined the influence of sampling frequency from chamber methods on reported annual emissions (Barton et al., 2015; Mishurov & Kiely, 2011; Savage, Phillips, & Davidson, 2014), research into determining and testing gap‐filling methods has been limited (Bigaignon, Fieuzal, Delon, & Tallec, 2020; Cowan et al., 2019; De Rosa et al., 2018; Taki, Wagner‐Riddle, Parkin, Gordon, & VanderZaag, 2018; Webb et al., 2019).…”
Section: Introductionmentioning
confidence: 99%